Performance Study of Wireless Systems with Switch and Stay Combining Diversity over α-η-μ Fading Channels - Eyadeh, A. A.; Al-Ta'ani, M. N. (Engineering, Technology & Applied Science Research, 2019)
In this paper, we consider a Switch and Stay Combiner (SSC) diversity scheme operating over α−η−μ fading channel. New and closed-form expressions for the average output SNR (ASNR), the moment-generating function (MGF), the outage probability (P_out), and the average symbol error rate (ASER) for M-ary quadrature amplitude modulation (QAM) signaling are derived. The expressions are obtained in terms of the well-known bivariate Fox’s H-function (BFHF). It is worth pointing out that the BFHF and the bivariate Meijer’s G-function (BMGF) have recently been used extensively in wireless communications literature to study the system's performance. The evaluated results are plotted for channel parameters of interest, and the effect of fading severity on the combiner performance is studied. Moreover, the results are shown to match those previously reported in the literature for other channel models such as η−μ as a special case, which confirms the validity of the obtained expressions. Also, insights on the optimal choice of the switching threshold are provided.